2002
DOI: 10.1136/bjo.86.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of clinical and histopathological parameters in conjunctival melanomas: a retrospective study

Abstract: Aim: To determine prognostic factors for recurrence of disease and tumour related mortality in patients with conjunctival melanoma. Methods: A retrospective analysis of clinical and histopathological data of 69 patients with histologically verified conjunctival melanoma. Results: As univariate analysis showed, significant risk factors for the development of recurrence were: irregular pigmentation (RR = 2.0, p = 0.0007), incomplete surgical excision (RR = 3.5, p = 0.008), tumour invasion deeper than in substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
4
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 13 publications
2
73
4
7
Order By: Relevance
“…5,27 Local tumour recurrence is reported to occur in more than 50% of these cases. 23,38,39 Risk factors for recurrence are reported to be: multifocal disease, non-limbal position of the tumour, involvement of the surgical margin, and surgical excision without adjunctive treatment. 27,40 Our rates of recurrence are only 1.5% at a median of 2.2 years for patients treated primarily at our centre and 1.9% at a median 1.6 years (range 0-6.98) for salvage therapy for patients who initially had surgery elsewhere.…”
Section: Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…5,27 Local tumour recurrence is reported to occur in more than 50% of these cases. 23,38,39 Risk factors for recurrence are reported to be: multifocal disease, non-limbal position of the tumour, involvement of the surgical margin, and surgical excision without adjunctive treatment. 27,40 Our rates of recurrence are only 1.5% at a median of 2.2 years for patients treated primarily at our centre and 1.9% at a median 1.6 years (range 0-6.98) for salvage therapy for patients who initially had surgery elsewhere.…”
Section: Prognosismentioning
confidence: 99%
“…8,27,39,41 Clinical risk factors include: disease recurrence, involvement of non-bulbar conjunctiva, medial bulbar conjunctiva, caruncle and plica semilunaris, and tumour thickness of more than 2 mm. 23,27,30,35,39,42 Clinically, CoMs are staged according to the 7th edition of TNM system developed by the AJCC and the International Union for Cancer Control (UICC). 7 Poor prognostic histopathological features comprise high mitotic count, presence of epithelioid cells, diffuse intraepithelial disease, extravascular matrix pattern, lymphatic invasion/microvascular density, lymphocytic/macrophage infiltration, and surface ulceration.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical prognostication Institution- 42,43 and populationbased [44][45][46] retrospective studies have consistently shown that the location and size of the primary conjunctival melanoma are strong and independent predictors of prognosis. Primary tumours located at the limbus, their most common site, or displaced to the cornea 47 carry a better prognosis than tumours in the bulbar, caruncular, and palpebral conjunctiva.…”
Section: Prognosis Of the Primary Tumourmentioning
confidence: 99%
“…1,5,16,[53][54][55][56][57] Prognostic factors include clinical features, with tumor location and extent being of major importance. Patients with multifocal tumors, orbital invasion, recurrent disease, and involvement of the caruncle, plica semilunaris, eyelid margins, and the palpebral and forniceal conjunctiva have a worse prognosis for survival.…”
Section: Prognostic Featuresmentioning
confidence: 99%